Introduction to cell mechanics and mechanobiology - Jacobs, C.R. (Christopher R.) (Garland Science, 2013)
"Introduction to Cell Mechanics and Mechanobiology teaches advanced undergraduate students a quantitative understanding of the way cells detect, modify, and respond to the physical properties within the cell environment. Coverage includes the mechanics of single molecule polymers, polymer networks, two-dimensional membranes, whole-cell mechanics, and mechanobiology, as well as primer chapters on solid, fluid, and statistical mechanics"